ドライバレー チイキ チョウサ ホウコク 1984-1985 - 小村, 和久; コムラ, カズヒサ; 中谷, 周; ナカヤ, シュウ; 森本, 隆夫; モリモト, タカオ; 鳥居, 鉄也; トリイ, テツヤ; Komura, Kazuhisa; Nakaya, Shyu; Morimoto, Takao; Torii, Tetsuya (1987)
P(論文) 1984-1985年のドライバレー地域における日本の地球化学チームの科学調査は大きく二つに分けられる。一つはCIROS計画への参加協力であり, 二つにはロス島を含むドライバレー地域の地球化学的, 環境科学的研究である。ドライバレー地域ではライト谷を中心に池の調査, 岩屑, 藻類などを採取したほかNaI(Tl)シンチレーションサーベィメータによる環境放射線レベルの測定を行った。このほか予備実験としてTLD(熱蛍光線量計)による積算線量の測定を実施した。そのほかスコット基地およびCIROS-2ドリルサイトにおいて大気浮遊塵を採取して大気中の宇宙線生成核種^7 と天然放射性核種^<210>Pbの測定を行った。 In the 1984-1985 summer season, science activities of Japanese geochemistry party are divided into two categories. The first one is the participation in the Cenozoic Investigations of the Western Ross Sea (CIROS) Project and the second one is the geochemical and environmental studies of the Dry Valleys region including the area near Scott Base in Ross Island. Water samples, ground surface detritus and algae were collected in this region from a limnological and environmental point of view. The sampling was made mostly in the North Fork and South Fork and the Labyrinth area in the Wright Valley. A NaI (Tl) scintillation survey meter was used to measure the environmental radiation level and a preliminary use of TLD (thermoluminescence dosimeter) was also made for monitoring the integral radiation dose. Concentrations of cosmic-ray induced ^8 and natural ^<210>Pb in surface air were measured for air dust samples collected at Scott Base and CIROS-2 drill site. departmental bulletin paper